Enhancing Urban Resilience: Mapping School Community Preparedness for Tsunami Disasters in Coastal Banda Aceh - Rizky, Muhammad Riza; Zuraidi, Evalina; Aulia, Fahmi (Popular Scientist, 2025)
Urban resilience against tsunami risks requires robust preparedness within educational institutions, particularly in high-risk coastal regions. This study assesses the disaster preparedness levels of senior high schools in the coastal districts of Meuraxa and Kuta Raja, Banda Aceh, employing a comprehensive mapping approach (LIPI-UNESCO/ISDR) to evaluate knowledge, preparedness policy, emergency planning, warning systems, and resource mobilization. Data were collected through questionnaires targeting school administrators, teachers, and students. The findings reveal significant disparities in preparedness levels, with SMAN 6 Banda Aceh demonstrating higher readiness compared to SMAS Al-Misbah, which exhibited the lowest scores across all dimensions. The absence of standardized disaster management policies and inadequate institutional preparedness were identified as critical challenges. The study underscores the urgent need for integrated disaster education, routine evacuation drills, and well-coordinated emergency response strategies to enhance school and community resilience. Furthermore, it advocates for a collaborative approach involving local authorities, educators, and disaster management agencies to embed disaster preparedness into the urban resilience framework. By mapping preparedness levels, this research provides actionable insights for policymakers to develop targeted interventions and promote sustainable disaster resilience strategies. Future research should expand to other vulnerable coastal areas and assess the long-term impacts of preparedness initiatives to ensure effective risk reduction.